A STUDY ON IMPACT OF SELECTED ONLINE SERVICES OF CANARA BANK ON CUSTOMER SATISFACTION - R S, Narendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Banks are the main suppliers of money and credit to the individuals, businesses, industries etc. The smooth functioning of the banking sector ensures a good and a healthy economy. The purpose of the paper is to reveal the impact of selected online services of Canara bank on customer satisfaction. 100 respondents who are using the online services of Canara Bank branches across Bangalore city. Structured questionnaire was issued to respondents includes the statements based on Liker Scale. Regression analysis was used as a statistical tool for the analysis of the selected constructs. The research results found that, the selected online services of Canara Bank such as Net Banking/ Online Payments, Bharat Bill Pay, Online Tax payments, PFMS through Net Banking and FA-STAG are having significant influence on customer satisfaction. Net Banking/ Online Payments services such as net banking facilities, view our details, and request cheque books or cards are the variables have significant impact on customer satisfaction in Canara Bank. Bharat Bill Pay services such as payment of utility bills, payment of school fees, and payment of municipal taxes, are the variables have significant influence on customer satisfaction in Canara Bank. Online Tax payments services such as E- payment of direct taxes, tax payment modes - internet banking, and online challan payments, are the variables have significant impact with customer satisfaction in Canara Bank. PFMS services such as, PFMS through Net Banking, Government efficiency effectiveness transparency, and curbing leakages and duplication, and are the variables have significant association with customer satisfaction in Canara Bank. FA-STAG services such as compact rechargeable tag for-toll plazas, quick transaction of fa-stag, and hassle-free fa-stag payment, and are the variables have significant influence on customer satisfaction in Canara Bank.